2022
DOI: 10.3389/fcvm.2022.851447
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nomogram and Risk Calculator for Postoperative Hypoxemia and Related Clinical Outcomes Following Stanford Type A Acute Aortic Dissection Surgery

Abstract: BackgroundHypoxemia is a common complication after Stanford type A acute aortic dissection surgery (AADS), however, few studies about hypoxemia after AADS exist. The aims of this study were to identify independent risk factors for hypoxemia after AADS and to clarify its association with clinical outcomes.MethodsPatients undergoing AADS from 2016 to 2019 in our hospital were identified and used as a training set. Preoperative variables were first screened by univariate analysis and then entered into a multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The presence of renal insufficiency, the serum levels of globulin, and surgical types were also identified to associate with the development of SH after HVS in our analysis, which was in agreement with some previous reports in other surgeries ( 3 , 7 , 8 ). Ge et al reported that patients undergoing surgery for type A aortic dissection had a 4.5-fold increased risk of postoperative hypoxemia compared to type B aortic dissection ( 8 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The presence of renal insufficiency, the serum levels of globulin, and surgical types were also identified to associate with the development of SH after HVS in our analysis, which was in agreement with some previous reports in other surgeries ( 3 , 7 , 8 ). Ge et al reported that patients undergoing surgery for type A aortic dissection had a 4.5-fold increased risk of postoperative hypoxemia compared to type B aortic dissection ( 8 ).…”
Section: Discussionsupporting
confidence: 92%
“…Three-quarters of the operations were isolated valve surgery, 13% had concomitant coronary artery bypass grafting (CABG), 11% had concomitant aortic surgery, and 2% had concomitant CABG as well as aortic surgery. The median durations of CPB and aortic cross clamp were respectively 108 (86, 139) and 72 (54, 95) min, and the volume of transfused RBC was 1 ( 1 , 3 ) units. The incidence rate of SH was 1.2% in isolated valve surgery, 2.7% in concomitant CABG, 7.0% in concomitant aortic surgery, and 20.6% in concomitant CABG and aortic surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several other predictors for postoperative hypoxemia have also been reported previously in the literature but were not found to be significant when analyzed by the multivariate analysis in the current study, such as advanced age, hypertension, smoking history, renal insufficiency, female sex, poor cardiac function, and diabetes ( 1 , 23 , 24 , 43 , 44 ). Some postoperative factors have also been reported to be related to the occurrence of postoperative hypoxemia, but we did not include postoperative factors into our analysis due to these factors were not available early.…”
Section: Discussionsupporting
confidence: 56%